ASME 2011 Summer Bioengineering Conference, Parts a and B 2011
DOI: 10.1115/sbc2011-53677
|View full text |Cite
|
Sign up to set email alerts
|

Progressive Post-Yield Behavior of Human Cortical Bone in Shear

Abstract: Bone fragility depends on its post-yield behavior since most of energy dissipation in bone occurs during the post-yield deformation. Previous studies have investigated the progressive changes in the post-yield behavior of human cortical bone in tension and compression using a novel progressive loading scheme. However, little is known regarding the progressive changes in the post-yield behavior of bone in shear. The objective of this short study was to address this issue by testing bone specimens in an inclined… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…Later torsional studies showed that damage appeared within interstitial bone, Haversian systems, and along cement lines [18,19]. However, since torsional tests generate non-uniform shear in the specimens, they are not suitable for 3 studying bone tissue behavior in pure shear mode [20,21]. More importantly, how shear induces microcracks within or between lamellae at the cortical bone level is still unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Later torsional studies showed that damage appeared within interstitial bone, Haversian systems, and along cement lines [18,19]. However, since torsional tests generate non-uniform shear in the specimens, they are not suitable for 3 studying bone tissue behavior in pure shear mode [20,21]. More importantly, how shear induces microcracks within or between lamellae at the cortical bone level is still unknown.…”
Section: Introductionmentioning
confidence: 99%
“…However, what actually happens during the post-yield deformation of bone at micro/ultrastructural levels is still poorly understood. As an effort to address the issue, we have studied the post-yield behavior of human cortical bone loaded under three distinct modes: tension (Wang and Nyman, 2007), compression (Leng et al, 2009), and shear (Dong et al, 2011) using a novel progressive loading scheme. These studies have shown that the post-yield behavior of bone is associated with an exponential decay of elastic modulus (micro-damage accumulation), linear plastic deformation, and an acute saturation of viscous behavior of the tissue (Nyman et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Table 2 Mechanical properties of cortical bone in tension and compression [24] The difference between the longitudinal and transverse creep curves of cortical bone has been shown in [26]. The anisotropic mechanical behavior of cortical bone under cyclic loading has been studied in [27][28][29][30]. Bone samples were prepared in the longitudinal, circumferential and radial directions of femur.…”
Section: Fig 5 Stress-strain Diagram Of Cortical Bone Under Cyclic mentioning
confidence: 99%